Cara Pengembangan Produk Minuman Mocktail Zeger – Zeger Melalui Kewirausahaan Merdeka (WMK) - Nadifah Salsabila (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
With the presence of universities, both private and state, every year they contribute expert staff to their graduating students. However, having a bachelor's degree does not necessarily guarantee that you will get a suitable job, sometimes many graduates are not all absorbed into the workforce, causing unemployment. The aim of this independent entrepreneurship program is to help students create income according to the students' abilities and competencies so that they can be independent, develop and not always depend on government assistance by helping to increase the continuity of the business the students are involved in. involved. For example, mocktail zeger - Zeger is a product produced from this program, high quality with a variety of flavors and toppings. In its implementation method, this program includes market research, marketing strategy, and logo creation. The conclusion states that in this business there is a large market opportunity by continuing to innovate and paying attention to the long-term interests of consumers.